PERANCANGAN KAPAL GENERAL CARGO 6800DWT KECEPATAN 10 KNOT DENGAN RUTE PELAYARAN BITUNG - TANJUNG PERAK - Aloisius Leonardo, (2020)
General cargo ship is a ship that carries a variety of cargo in the form of goods. The goods transported are usually packaged goods. General cargo ships are equipped with cargo cranes to facilitate loading and unloading. This study was conducted to design a 6800 DWT cargo ship with a speed of 10 knots for the Bitung - Surabaya shipping route. The method used is to use a comparative ship to produce the main size of the ship. This comparative method design uses 2 comparative ship data obtained from the BKI register in this study, the principal sizes obtained are as follows: LOA = m, LPP = m, B = m, H = m, T = m, Cb =, Cp =, Cw =. The design of this ship is carried out in several stages, such as finding suitable comparative ships to make line plans, general plans, hydrostatic analysis, ship resistance analysis, ship stability, ship strength. And others.